MENINGKATKAN KETERAMPILAN GENERIK SAINS DAN KEJUJURAN SISWA MELALUI MODEL KOOPERATIF BERBASIS BUDAYA ACEH - Fitri Handayani; Zulfahmi .; Nelliraharti . (JOURNAL OF EDUCATION SCIENCE, 2020)
AbstractThe purpose of this study is (1) to improve generic science skills through an Aceh-based cooperative culture model on physics material. (2) Increase the honesty of students in the learning process through a cooperative culture based in Aceh. (3) To improve students' understanding of culture. The sample of this study was taken 1 (one) class. The research sample was applied to students of class XI IPA 1 Kutacane 1, Bambel sub-district, Aceh Tenggara district, which consisted of 37 students. Classes will be applied to learning through Acehnese culture-based cooperative learning models. Data collection techniques through generic science skill observation sheets are expressed in the number of mean values, and N-Gain values. Data processing to measure student honesty is to calculate the percentage of each indicator of student honesty questionnaire. Student response data were obtained using the student response questionnaire. The results of the study enhance students' generic science skills through a cooperative model based on Aceh culture physical material with a normal gain of 0.72 in the high category. Honesty students are obtained using an honest questionnaire, the openness of teachers and students in the learning process can improve students' sense of honesty. The positive response of students reaches 90.8%.  Keywords:Cooperative based on Aceh culture, generic science skills, Honesty of Students